m6A Modification in Mammalian Nervous System Development, Functions, Disorders, and Injuries - Yu, Jun; She, Yuanchu; Ji, Sheng-Jian (Frontiers in Cell and Developmental Biology, 2021)
N6-methyladenosine (m6A) modification, as the most prevalent internal modification on mRNA, has been implicated in many biological processes through regulating mRNA metabolism. Given that m6A modification is highly enriched in the mammalian brain, this dynamic modification provides a crucial new layer of epitranscriptomic regulation of the nervous system. Here, in this review, we summarize the recent progress on studies of m6A modification in the mammalian nervous system ranging from neuronal development to basic and advanced brain functions. We also highlight the detailed underlying mechanisms in each process mediated by m6A writers, erasers, and readers. Besides, the involvement of dysregulated m6A modification in neurological disorders and injuries is discussed as well.